Growing population segments and their impact on future transport - Haustein, Sonja; Nielsen, Thomas Alexander Sick; Siren, Anu (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
The European population is facing enormous demographic changes. Based on data from the Danish National Travel Survey (NTS), this paper focuses on three major societal trends – changing family structures, ageing, and urbanisation – and the impact of these trends on future car use in Denmark. We compared the mode choice of single parents and people in single person households (both in “family age” and after retirement) with the choice of people in more traditional household forms. Additionally, we looked into differences within these groups related to gender and urban from. The relevance of these variables for car use as driver, as passenger, and in total was estimated in linear regression analyses. Persons living alone showed the lowest car use; living with a partner and having kids increased driving. While gender differences in older people’s car use could partly be explained with women’s lower car availability and driving licence rates, this was not the case for younger people. Thus, gender roles and different travel preferences are expected to play a role here. Living in a large urban area significantly decreased car use of younger people, whereas it increased older people’s car use as passenger. The lower driving rates of singles and single parents compared to couples with children could be explained with differences in car availability. When this was controlled for, single parents used the car as often as couples with children. To what extent the mobility needs of single parents are met satisfactorily without a car and whether they could serve as a model for car-free living are among the questions that cannot be answered based on the NTS data but should be addressed in future research.